ANALYZING THE EFFECT OF CONSUMERS EMOTIONS ON CONSUMER BEHAVIOR AT MATAHARI DEPARTMENT STORE MANADO - Makarawung, Evanglin M.; Mekel, Peggy A.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2014)
Companies have to face all of challenge that happen, utilize all of opportunity and understand all of needs and wants of consumers to get a win in business competition. Development of Department Store in Indonesia showed significant figures in line with the increasing of needs toward fulfillment of a fairly large of consumers’ needs. Emotions are important factor in studying consumption, consumer decision making and consumer behavior. The purpose of this study is to analyze the effect of positive and negative emotions simultaneously and partially. The research method is associative with the analysis technic is multiple linear regression. Consumers who buy and visit at Matahari Department Store Manado are the population of this study and researcher collected 100 respondents as a sample. The result showed both positive and negative emotion effect very significantly on consumer behavior simultaneously and partially. Researcher recommended for management of Matahari Department Store Manado to pay attention deeply on consumers’ emotions. Keywords: emotions, retail management, consumer behavior.